2011
DOI: 10.4100/jhse.2011.62.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combined program of physical activity and intellectual activity in the cognitive functioning of the elderly

Abstract: Martínez-Vidal A, Prada A, Díaz MP, Martínez-Patiño MJ. Effect of a combined program of physical activity and intellectual activity in the cognitive functioning of the elderly. J. Hum. Sport Exerc. Vol. 6, No. 2, pp. 462-473, 2011. Aerobic exercise done in an enriched environment with intellectual activity seems to improve cognitive performance associated with the aging process of humans, although the results can sometimes be contradictory. The objective of the present study was to ascertain to what degree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
1
0
3
Order By: Relevance
“…Specifically, cognitive decline is higher among those participants who are 80 years or older, being more expressive after 85 years. This result fits with several studies that show that there is a general cognitive decline with age, even though age is not the referred as the main factor ( Hooren et al, 2007 ; Bourne et al, 2010 ; Martínez-Vidal et al, 2011 ; Oliveira et al, 2011 ). This cognitive decline can be explained, to a certain point, by the high rate of illiteracy and of lower education in the elderly aged 85 or more, and also by the high number of retired and inactive elderly within this age group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, cognitive decline is higher among those participants who are 80 years or older, being more expressive after 85 years. This result fits with several studies that show that there is a general cognitive decline with age, even though age is not the referred as the main factor ( Hooren et al, 2007 ; Bourne et al, 2010 ; Martínez-Vidal et al, 2011 ; Oliveira et al, 2011 ). This cognitive decline can be explained, to a certain point, by the high rate of illiteracy and of lower education in the elderly aged 85 or more, and also by the high number of retired and inactive elderly within this age group.…”
Section: Discussionsupporting
confidence: 91%
“…Research has shown that both the prevalence and the rate of dependency increase with age ( Espigares et al, 2008 ; Espelt et al, 2010 ) and that dependency is associated with several factors as cognitive impairment, depression, neurological diseases, back, neck and shoulders pain, osteoarthritis, chronic back problems, osteoporosis, more medication, lower economic resources ( Murtagh and Hubert, 2004 ; Formiga et al, 2007 ; Santos et al, 2007 ; Schneider et al, 2008 ; Nunes et al, 2010 ). On the other hand age is not the most important factor for cognitive impairment measured by the Mini Mental State Examination (MMSE; Green et al, 2008 ; Karlamangla et al, 2009 ), but it has been found a global decline in cognitive functioning with age ( Hooren et al, 2007 ; Bourne et al, 2010 ; Martínez-Vidal et al, 2011 ). Beyond age, other factors have been associated to cognitive decline in old people, as gender, marital status, education, social support network, socioeconomic status, and lifestyle ( Hooren et al, 2007 ; Karlamangla et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…al. 2019; Chulhwan Choi, Chul-Ho Bum, 2019; Martínez-Vidal A., Martínez A. P., Del Pino Díaz Pereira M., Martínez-Patiño M. J., 2011;Monteiro, A.M., Silva, P., Forte, P., & Carvalho, J., 2019). Also, researchers Pliukhina G.A., Tikhonova T.V., Hakman A.V., Pangelova N.E.…”
Section: Introductionunclassified
“…La inclusión e importancia que se les atribuye a los adultos mayores (AM) ha tenido cambios significativos, esto ha estado condicionado por múltiples factores ya que el envejecimiento es un proceso natural acompañado de un deterioro estructural y funcional con aparente disminución en los diferentes dominios, lo que afecta la autonomía personal y calidad de vida para los adultos mayores. (Martínez, Prada, Díaz & Martínez-Patiño, 2011).…”
Section: Introductionunclassified